The young star cluster population of M51 with LEGUS: II. testing environmental dependences - Messa, Matteo; Reina-Campos, Marta; Gouliermis, Dimitrios A.; Grebel, Eva K.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. It has recently been established that the properties of young star clusters (YSCs) can vary as a function of the galactic environment in which they a
Gesehen am 06.02.2019